(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aims to present Chromobacterium violaceum isolated from a pleural effusion in an indoor-outdoor cat. Materials and Methods: A 3-year-old male domestic shorthair cat was brought to the hospital with dyspnea. The thoracic radiographs and ultrasound showed the presence of a pleural effusion. The thoracic fluid was sent for cytological analysis, reverse transcription polymerase chain reaction (RT-PCR) for feline infectious peritonitis (FIP), and bacterial culture. Results: Cytological findings illustrated the protein-rich modified transudate. Albumin: globulin ratio was 0.4. RT-PCR testing for FIP was negative. The bacterial culture presented a pure growth of violet-pigmented colonies on both sheep blood agar and MacConkey agar. The isolation was identified and further confirmed as C. violaceum. The isolation was susceptible to drugs in aminoglycosides, tetracyclines, macrolides, fluoroquinolones, and sulfonamide groups. Conclusion: Chromobacterium violaceum, a saprophytic Gram-negative bacterium, commonly inhabits stagnant water and soil in tropical and subtropical areas. It is considered an opportunistic bacterium in both veterinary and human medicine. Although C. violaceum infection is rare, the disease is extremely fatal. In Thailand, a few cases of humans infected with C. violaceum were reported; however, the bacterial infection has never been discovered in animals. This case report highlighted a rare opportunistic infection of C. violaceumin a cat in Thailand and suggested drugs of choice for clinical treatments. J. Adv. Vet. Anim. Res., 12(1): 297–302, March 2025 http://doi.org/10.5455/javar.2025.l896